PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN MENULISTEKS BERITA PADA SISWA KELAS VII SMP SWASTA METHODIST 9 MEDAN - Elma Natalia Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low ability of students to write news texts, which is indicated by difficulties in structuring news, completing the 5W + 1H elements, and applying linguistic rules correctly. This study aims to describe the application of the Contextual Teaching and Learning (CTL) model, student activities during learning, and the level of students' ability to write news texts after participating in learning with the CTL model. The study used mixed methods with qualitative and quantitative approaches. Qualitative data were obtained through observations of the application of the CTL model and student activities, while quantitative data were obtained through a test of news text writing skills. The subjects were seventh-grade students of Methodist 9 Private Middle School, Medan. Qualitative data were analyzed descriptively, while quantitative data were analyzed using descriptive statistics and the Mann–Whitney U test. The results showed that the application of the CTL model was implemented in the very good category with an implementation percentage of 95.23%. Student activities during learning were also in the very good category because students were actively involved in each component of CTL, namely constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. The students' ability to write news texts after participating in learning with the CTL model obtained an average score of 92.93 with a very good category, while the class using conventional learning obtained an average score of 70.43. The results of the Mann–Whitney U test showed a significance value <0.05, so there was a significant difference between the ability to write news texts of students who learned using the CTL model and students who learned with conventional learning. Thus, the CTL model is effective for use in learning to write news texts.